Dynamic phasor analysis and design of phase-locked loops for single phase grid connected converters - Rashed, Mohamed; Klumpner, Christian; Asher, Greg (Emerald, 2015)
The purpose of the paper is to introduce the Dynamic Phasor Modelling (DPM) approach for stability investigation and control design of single-phase Phase Locked Loops PLLs. The aim is to identify the system instabilities not predicted using the existent analysis and design methods based on the simplified average model approach.